Design of Composite Structures Using Advanced Numerical Tools - Kulhavy, Petr; Lepsik, Petr (Manufacturing Technology Journal, 2018)
The main topic of the presented paper is review of the mostly used tools in designing of composite structures. Consequently, practical demonstration of their using has been done on an example of a bending test of the wound, thin-walled composite rod. Further methods of definitions individual layers and the associated interface properties using the cohesive elements, based on that it is possible to detect arising delamination. Unlike conventional approaches, there is not possible to define a definite strength limit or nonlinear plasticity. For this purpose, the so-called failure criteria exist for the composite materials. In this way, it is possible to describe the real stress/ strain situation for the composite parts. Composite materials, due to their anisotropy, offer by suitable layer composition the possibility of significantly improving the efficiency of material utilization. Just in such cases, some advanced numerical tools like e.g. DOE, response surface and genetic algorithms could be used. Based on the above described methods, the experimental results of the carried three point flexure test have been numerically verified and the properties of the tested rod optimized.
Keywords: Composite Materials; Carbon Fibers; Bending Test; Design of Experiments; Failure Criteria